SELECTION AND TALENT MANAGEMENT IN THE SOCCER ACADEMY OF DEBRECEN, HUNGARY - Kónya, Bence; Lenténé Puskás, Andrea (Stadium - Hungarian Journal of Sport Sciences, 2020)
The aim of this study is to deal with the survey of the selection and the system of talent management through the example of the Debrecen Soccer Academy. In connection with this topic we analyzed international and Hungarian articles, in addition we examined the structure, operation and role of the youth age players. It is not an easy task to recognise the talent of the players. The selection of talented sportsman is a very complex process during which you must consider many aspects such as human biological characteristics, physiological and sociological factors. Psychological and cognitive factors are also decisive. Several studies prove that being successful as an adult can be predicted at a young age.